Comparative Toxicity and LC50 Determination of Phaleria macrocarpa Leaf Extracts from Sequential Maceration - Rahmat Dwi Alamsyah; Trirakhma Sofihidayati; Irfan Zamzani; Noverda Ayuchecaria; Sari Wulan Asih; Sara Nurmala (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Phaleria macrocarpa is a plant renowned for its bioactive compounds, including flavonoids, alkaloids, saponins, and tannins, which are believed to have various pharmacological properties. This study aimed to determine the lethal concentration 50 (LC50) of P. macrocarpa leaf extracts obtained by sequential maceration in n-hexane, ethyl acetate, and 70% ethanol. The toxicity of the extracts was evaluated using the Brine Shrimp Lethality Test (BSLT) against Artemia salina leach larvae, a commonly used model organism in toxicity testing due to its sensitivity to various toxic substances. The results indicated that the 70% ethanol extract exhibited moderate toxicity with an LC50 of 126.981 ppm, the ethyl acetate extract was categorized as weakly toxic (LC50 of 691.730 ppm), and the n-hexane extract was classified as non-toxic (LC50 of 1416.537 ppm). These findings indicate that solvent polarity influences the extraction of bioactive compounds and their biological activity. This study highlights the novelty of sequential maceration as a selective extraction approach that enhances toxicity profiling and supports preliminary pharmacological screening for natural product-based drug development. Furthermore, the study underscores the importance of using selective extraction methods to isolate bioactive compounds based on their polarity. This study provides preliminary data on the toxicity profile of P. macrocarpa leaves and highlights the potential of its bioactive compounds for further pharmacological research, particularly in the development of natural-based therapeutic agents. Future studies should focus on isolating and identifying the active compounds responsible for the observed toxicity and on their potential for use in drug development.